METODE KPU KOTA PEKANBARU DALAM MENINGKATKAN PARTISIPASI PENYANDANG DISABILITAS PADA PEMILIHAN UMUM TAHUN 2024 - Abda, Muhammad Faiz; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
In the 2024 general election, the percentage of participation of persons with disabilities was 73%. Compared to the 2019 general election, their participation percentage was only 33%. This research aims to determine the methods used by the Pekanbaru City KPU in increasing the political participation of persons with disabilities. The theory used to examine this research is the theory according to L. Schur, M. Adya, and M. Ameri (2015) which states that there are four methods to increase the political participation of persons with disabilities. This research employs a mixed-methods approach. KPU used several methods to increase the participation of persons with disabilities in the 2024 general election. First, improving the accessibility of polling stations and voting equipment. Second, mobile voting was implemented. Third, training for polling station officers. Fourth, socialization and political education for persons with disabilities. Keywords: Disability, General Election Commission, Participation